Randomized «FARVATER» study. Atorvastatin (10 and 20 mg/d) in treating patients with coronary heart disease and dyslipidemia: effects on lipids, C-reactive protein and fibrinogen levels - A. V. Susekov; M. Yu. Zubareva; M. I. Tripoten’; T. A. Rozhkova; O. A. Pogorelova; T. V. Balakhonova; V. P. Masenko; V. V. Kukharchuk (Кардиоваскулярная терапия и профилактика)
Aim. To compare effects of atorvastatin in the doses of 10 and 20 mg/d on lipid profile, C-reactive protein (hsCRP), fibrinogen levels, as well as vascular wall structure and function in patients with coronary heart disease (CHD) and primary hyperlipidemia (PHL). Material and methods. Fifty CHD and PHL patients were randomized to 10 or 20 mg/d atorvastatin doses (no titration), for 24-week period. Atorvastatin effects on lipids, treatment tolerability (symptoms ± increased hepatic enzymes), as well as on endothelial function, vessel elasticity and stiffness, were examined. Results. After 24 weeks of 10 mg/d atorvastatin treatment, levels of total cholesterol (TCH), triglycerides (TG), and low-density lipoprotein CH (LDL-CH) significantly decreased – by 25,4%, 21,7%, 34,9%, respectively. In 20 mg/d group, these figures were 27%, 15,2%, and 43,9%, respectively. No significant inter-group difference in LDL-CH levels was registered. No substantial CRP and fibrinogen level reduction was observed. During 24 weeks, 7 adverse events were registered, only 2 (4%) being related to atorvastatin therapy. Conclusion. In patients with CHD and PHL, atorvastatin (10-20 mg/d) decreased LDL-CH levels by 35-44%, and was well-tolerated. The therapy did not affect hsCRP and fibrinogen levels.